The cinema as a teaching tool in psychology - Arboccó de los Heros, Manuel (2018)
In the next article, we will share some thoughts –by way of headings– on the psychological  analysis of films as a tool in the university chair. Both the cinema (such as the theater and, of course, books) are ways that the man has to learn, think, grow as a person and culturizarse; and are tools that can and should be incorporated in the teaching practice. We have chosen some good movies to provide an example of exercise of psychological analysis. We hope will be of interest and invite reflection